2003
DOI: 10.1074/jbc.m306538200
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Mass-action Mechanism Explains Capacitative Calcium Entry in Jurkat and Skeletal L6 Muscle Cells

Abstract: We examined capacitative calcium entry (CCE) in Jurkat and in L6 skeletal muscle cells. We found that extracellular Ca 2؉ can enter the endoplasmic reticulum (ER) of both cell types even in the presence of thapsigargin, which blocks entry into the ER from the cytosol through the CaATPase. Moreover, extracellular Ca 2؉ entry into the ER was evident even when intracellular flow of Ca 2؉ was in the direction of ER to cytosol due to the presence of caffeine. ER Ca 2؉ content was assessed by two separate means. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…We confirmed the dye method for SR Ca 2þ measurement by incorporating a Ca 2þ sensor protein into the SR by transfection. 40 Experiments in the present study further support this view. Figure 5 shows that the SR lumen of the L6 cells accumulates extracellular Ca 2þ even in the presence of both thapsigargin as well as high concentrations of Ry, so that no exchange with cytosolic Ca 2þ is possible.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We confirmed the dye method for SR Ca 2þ measurement by incorporating a Ca 2þ sensor protein into the SR by transfection. 40 Experiments in the present study further support this view. Figure 5 shows that the SR lumen of the L6 cells accumulates extracellular Ca 2þ even in the presence of both thapsigargin as well as high concentrations of Ry, so that no exchange with cytosolic Ca 2þ is possible.…”
Section: Discussionsupporting
confidence: 81%
“…In previous studies, we have provided evidence for a direct interaction of the DHPR and the RyR to explain SOCE. 11,12 We suggested that these two Ca 2þ channels together form a combined channel for the direct entry of Ca 2þ from the extracellular space to the SR lumen. As this process occurs in resting (polarized) conditions, the DHPR is static in location, directly facing (and occupying) an RyR.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, the question of coupling of stores and extracellular medium is unsettled even for rather intensely investigated cells, such as lymphocytes, for which recently Narayanan et al [50] have postulated a direct mass-action mechanism to explain the rapid capacitative calcium entry into the ER. This would require influx channels in the cell membrane matching with juxtaposed channels in the ER membrane.…”
Section: Could a Cation Antiporter Account For A Rapid Calcium Transimentioning
confidence: 99%
“…Because ER, NE, and Golgi are major constituents of the intracellular Ca 2ϩ store (2,3,21), the ER-PM fusion sites may allow Ca 2ϩ entry from the extracellular space directly into the store lumen. Although the store can be effectively replenished from the cytosol via Ca 2ϩ -ATPase (22), a recent study demonstrated that in Jurkat T cells, the store can be refilled in the absence of sarco-endoplasmic reticulum calcium ATPase pump activity (23). Direct Ca 2ϩ flow from the extracellular space into the ER might complement the Ca 2ϩ -ATPase refilling pathway and might be important for both Ca 2ϩ signaling and protein handling within intracellular organelles.…”
Section: Fm1-43 Spreads From the Peripheral Er Toward Ne And Golgi-mentioning
confidence: 99%